Drought and salinity induced changes in ecophysiology and proteomic profile of Parthenium hysterophorus. - Javed Ahmad; Humayra Bashir; Rita Bagheri; Affan Baig; Asma Al-Huqail; Mohamed M Ibrahim; M Irfan Qureshi (PLoS ONE, 2017)
Parthenium hysterophorus is a plant that tolerates drought and salinity to an extremely high degree. Higher expression of stress-responsive proteome contributes for greater defence against abiotic stresses. Thus, P. hysterophorus could be a rich source of genes that encode stress-imparting mechanisms and systems. The present study utilizes comparative physiological and proteomic approaches for identification of key proteins involved in stress-defence of P. hysterophorus. Thirty-days-old plants were exposed to drought (10% PEG 6000) and salinity (160 mM NaCl) for 10 days duration. Both stresses induced oxidative stress estimated in terms of TBARS and H2O2. Levels of both enzymatic and non-enzymatic antioxidants were elevated, more by drought than salinity. Particularly, SOD, GR, CAT and GST proved to be assisting as very commendable defence under drought, as well as salinity. Levels of ascorbate, glutathione and proline were also increased by both stresses, more in response to drought. Comparative proteomics analysis revealed a significant change in relative abundance of 72 proteins under drought and salinity. Drought and salinity increased abundance of 45 and 41 proteins and decreased abundance of 24 and 26 proteins, respectively. Drought and salinity increased and decreased abundance of 31 and 18 proteins, respectively. The functions of identified proteins included those related to defence response (26%), signal transduction (13%), transcription and translation (10%), growth and development (8.5%), photosynthesis (8.5%), metabolism (7%), terpenoid biosynthesis (5.5%), protein modification and transport (7%), oxido-reductase (4%) and Miscellaneous (11%). Among the defence related proteins, antioxidants and HSPs constituted 26% and 21%, respectively. Present study suggests a potential role of defence proteins. Proteins involved in molecular stabilization, formation of osmolytes and wax and contributing to stress-avoiding anatomical features emerged as key and complex mechanisms for imparting stress tolerance to P. hysterophorus.